Disruptions Control on Precast Concrete Supply Chain in Construction Projects - Marie, Iveline Anne; Nilla, N.; Azmi, Nora; Suprana, Yayang Ade (Jurnal Ilmiah Teknik Industri, 2020)
Agility amid uncertain circumstances is key to all-across sustainable industries, and the construction industry depends heavily on projects as potent drivers to their operational activities regardless of projects’ hardwired constraints—shipment, resistance to risks— to affect Key Performance Indicator (KPI). PT ABX as one of Indonesian precast-concrete manufactures is the object of this research aiming to find precautionary strategies for controlling disruptions to concrete supply chain in construction projects. It takes into account such supply-chain disruptions, and therefore, the two-layered model of House of Risk (HOR) to subsume risks identification and risks control is applicable for minimizing possible disruptions. It finds risk events some of which are classified as critical risk events and preventive actions against risks. The findings contribute to working framework for managers responsible for applying effective strategies for preventing such disruptions.